2017
DOI: 10.1089/wound.2017.0737
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Approach to Quantitatively Measure Residual Limb Skin Health in Individuals with Lower Limb Amputation

Abstract: Objective: (1) Develop a standardized approach to quantitatively measure residual limb skin health. (2) Report reference residual limb skin health values in people with transtibial and transfemoral amputation. Approach: Residual limb health outcomes in individuals with transtibial (n = 5) and transfemoral (n = 5) amputation were compared to able-limb controls (n = 4) using noninvasive imaging (hyperspectral imaging and laser speckle flowmetry) and probe-based approaches (laser doppler flowmetry, transcutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
(27 reference statements)
2
14
0
Order By: Relevance
“…A recent study was the first to directly test the effect of EVS on residual-limb skin health and blood flow [20]. This study used a standardized non-invasive imaging (Figures 4-7) approach with a combination of out-of-socket imaging (e.g., hyperspectral imaging, transepidermal water loss (TEWL) and surface electrical capacitance (SEC)) and in-socket imaging (e.g., transcutaneous oximetry (TCOM), laser Doppler flowmetry (LDF)) [20,33]. Outcomes of this study identified that elevated vacuum suspension socket systems promote better residual limb skin physiology by preserving the skin barrier function (TEWL measurements), rescuing against loss of tissue oxygenation during activity and attenuating reactive hyperemia.…”
Section: Surface Electrical Capacitance For Skin Hydration (A) Closementioning
confidence: 99%
See 3 more Smart Citations
“…A recent study was the first to directly test the effect of EVS on residual-limb skin health and blood flow [20]. This study used a standardized non-invasive imaging (Figures 4-7) approach with a combination of out-of-socket imaging (e.g., hyperspectral imaging, transepidermal water loss (TEWL) and surface electrical capacitance (SEC)) and in-socket imaging (e.g., transcutaneous oximetry (TCOM), laser Doppler flowmetry (LDF)) [20,33]. Outcomes of this study identified that elevated vacuum suspension socket systems promote better residual limb skin physiology by preserving the skin barrier function (TEWL measurements), rescuing against loss of tissue oxygenation during activity and attenuating reactive hyperemia.…”
Section: Surface Electrical Capacitance For Skin Hydration (A) Closementioning
confidence: 99%
“…Data are mean perfusion units ± SE (shown as error bar). *p<0.05 O vs I within gp at time point (reprinted with permission from Rink CL et al[33]).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Residual limb TcPO2 in persons with a lower limb amputation is considerably reduced. Rink et al compared resting TcPO2 levels in five persons with a transtibial amptuation (four due to trauma, one due to infection) while wearing and not wearing a liner [26]. It is unknown whether the participants had any undelying conditions such as PAD or were suffering from RLP.…”
Section: Introductionmentioning
confidence: 99%